Free radical degradation in aqueous solution by blowing hydrogen and carbon dioxide nanobubbles - Toyohisa Fujita; Hiromi Kurokawa; Zhenyao Han; Yali Zhou; Hirofumi Matsui; Josiane Ponou; Gjergj Dodbiba; Chunlin He; Yuezou Wei (Scientific Reports, 2021)
Abstract The main findings are the hydroxyl radical scavenging and the superoxide anion diminishing by mixing the carbon dioxide (CO2) nanobubbles after hydrogen nanobubble blowing in water and alcohol aqueous solution. The nanobubbles produce the hydroxyl radical by ultrasonic waves, changing the pH and catalyst and so on, while the nanobubble is very reactive to scavenge free radicals. In this research especially hydrogen (4% H2 in argon) and CO2 nanobubbles have been blown into hydrogen peroxide (H2O2) added pure water, ethanol, and ethylene glycol aqueous solution through a porous ceramic sparger from the gas cylinder. The aqueous solutions with H2O2 are irradiated by ultraviolet (UV) light and the produced hydroxyl radical amount is measured with spin trapping reagent and electron spin resonance (ESR). The CO2 nanobubble blowing extremely has reduced the hydroxyl radical in water, ethanol, and ethylene glycol aqueous solution. On the other hand, when H2 nanobubbles are brown after CO2 nanobubble blowing, the hydroxyl radical amount has increased. For the disinfection test, the increase of hydroxyl radicals is useful to reduce the bacteria by the observation in the agar medium. Next, when the superoxide anion solution is mixed with nanobubble containing water, ethanol, and ethylene glycol aqueous solution, H2 nanobubble has reduced the superoxide anion slightly. The water containing both CO2 and H2 nanobubble reduces the superoxide anion. The less than 20% ethanol and the 30% ethylene glycol aqueous solution containing CO2 nanobubbles generated after H2 nanobubble blowing can diminish the superoxide anion much more. While the H2 nanobubble blowing after CO2 nanobubble blowing scavenges the superoxide anion slightly. The experimental results have been considered using a chemical reaction formula.